Functional capacity and risk of falls in the elderly with metabolic syndrome - Soares, Ramon Repolês; Salgado, Patrícia de Oliveira; Rocha, Kelvin Oliveira; Lima, Luciana Moreira (Revista brasileira de medicina de família e comunidade, 2020)
Introduction: Metabolic syndrome (MetS) is the most common metabolic abnormality in the population that predisposes to cardiovascular events and may be related to poor physical fitness and low functional capacity in the elderly. The objective of this study was to evaluate the interference of metabolic changes in functional capacity and risk of falls in the elderly. Methods: A cross-sectional study was carried out with 126 elderly subjects, 58 presented MetS and 68 without MetS, according to the criteria of the International Diabetes Federation. Katz Index, Tinetti Index, Timed Up and Go test and Berg Scale were applied to evaluate the functional capacity. Falls Efficacy Scale-International scale (FES-I-Brazil) was used to evaluate the fear of falling. For statistical analysis, the Mann-Whitney, Chi-square and Spearman correlation tests were used. Results: There was an association between the MetS and non-MetS groups in relation to the risk strata of the TUG index [p=0.02; OR=0.38; 95%CI (0.16-0.91)]. Between these two groups, there was a significant difference in the mean of the following markers: Berg scale (p=0.03); TUG (p=0.03); FES-I-Brazil (p=0.02). The Kats and IPAQ index did not show any significant association. Conclusions: Elderly patients with MetS presented higher risk and fear of falls when compared to patients without MetS. However, there was no variation in walking ability or balance.